The Potential Risk Factors for Mortality in Patients After In-Hospital Cardiac Arrest: A Multicenter Study - Wang, Mei-Tzu; Huang, Wei-Chun; Yen, David Hung-Tsang; Yeh, En-Hui; Wu, Shih-Yuan; Liao, Hsun-Hsiang (Frontiers in Cardiovascular Medicine, 2021)
Background and Purpose: In-hospital cardiac arrest (IHCA) has high mortality rate, which needs more research. This multi-center study aims to evaluate potential risk factors for mortality in patients after IHCA. Methods: Data for this study retrospectively enrolled IHCA patients from 14 regional hospitals, two district hospitals, and five medical centers between 2013 June and 2018 December. The study enrolled 5,306 patients and there were 2,871 patients in subgroup of intensive care unit (ICU) and emergency room (ER), and 1,894 patients in subgroup of general wards. Results: As for overall IHCA patients, odds ratio (OR) for mortality was higher in older patients (OR = 1.69; 95% CI:1.33–2.14), those treated with ventilator (OR = 1.79; 95% CI:1.36–2.38) and vasoactive agents (OR = 1.88; 95% CI:1.45–2.46). Whereas, better survival was reported in IHCA patients with initial rhythm as ventricular tachycardia (OR = 0.32; 95% CI: 0.21–0.50) and ventricular fibrillation (OR = 0.26; 95% CI: 0.16–0.42). With regard to ICU and ER subgroup, there was no mortality difference among different nursing shifts, whereas for patients in general wards, overnight shift (OR = 1.83; 95% CI: 1.07–3.11) leads to poor outcome. Conclusion: For IHCA patients, old age, receiving ventilator support and vasoactive agents reported poor survival. Overnight shift had poor survival for IHCA patients in general wards, despite no significance in overall and ICU/ER subgroups.